2008
DOI: 10.1093/ejo/cjm115
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of arch length based on intercanine width

Abstract: Arch length (AL), intercanine width (ICW), and intermolar width (IMW) are essential for diagnosis and treatment planning and are closely related factors in orthodontics. The aim of the present study was to determine correlations between these measurements and to predict some of these measurements based on others. The dental casts of 197 Spanish patients (119 females and 78 males) with a mean age of 18 years (11-26 years) in the permanent dentition attending the Orthodontic Department of the University of Valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
1
15
1
Order By: Relevance
“…Similar values are reported for nontreated patients by Paulino [12], Forster [26] and Tibana [27], who also showed that this measurement commonly is stable in adults over a period of 7 years.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar values are reported for nontreated patients by Paulino [12], Forster [26] and Tibana [27], who also showed that this measurement commonly is stable in adults over a period of 7 years.…”
Section: Discussionsupporting
confidence: 87%
“…This parameter was chosen, because the canine-distance is more convenient to measure during the daily clinic routine of an orofacial myologist rather than the intermolar distance. Yet it gives significant information about the dental arch development [12,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of method that is the focus of this study is a mathematical one that uses multiple regression analysis to develop an equation for estimating arch perimeter, as described by Sanin et al, 22 Paulino et al 23 and Al-Khatieeb et al 24 This method involves analysis of the relationship between arch lengths, widths, and perimeters.…”
Section: Introductionmentioning
confidence: 99%
“…This equation is believed to be accurate. In 2008, Paulino et al 23 proposed a regression equation that utilized inter-canine width to predict arch perimeter (referred to as arch length in their article): Arch length (perimeter) = (1.36 × inter-canine width) + 29.39. In 2014, Al-Khatieeb et al 24 tried to predict arch perimeter based on dental arch width at the level of each tooth: 35.…”
Section: Introductionmentioning
confidence: 99%